2012
DOI: 10.1111/j.1746-1561.2012.00711.x
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Socio‐Ecological Factors and Having an After‐School Physical Activity Program

Abstract: Having an after-school PA program was associated with personal and environmental factors, which supports the use of socio-ecological frameworks for explorative and intervention studies aiming to increase after-school PA programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Previous research investigated the association of the prevalence rate of obesity in adolescents with socio-economic status such as annual house hold income, sex, race and ethnicity. The studies reported that the rates of obesity were greater in African American and Hispanic adolescents than in their white counterparts [ 35 , 36 ]. The higher rate of obesity in minority adolescents is known to be related to socioeconomic status in complex ways [ 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research investigated the association of the prevalence rate of obesity in adolescents with socio-economic status such as annual house hold income, sex, race and ethnicity. The studies reported that the rates of obesity were greater in African American and Hispanic adolescents than in their white counterparts [ 35 , 36 ]. The higher rate of obesity in minority adolescents is known to be related to socioeconomic status in complex ways [ 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The studies reported that the rates of obesity were greater in African American and Hispanic adolescents than in their white counterparts [35,36]. The higher rate of obesity in minority adolescents is known to be related to socioeconomic status in complex ways [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the teachers proposed improving the connection of all the intervention areas that we have mentioned above, apart from creating other additional opportunities for practice. Therefore, we place emphasis on the need to organize the practice of PA after school (33,34). The challenge, in this sense, to achieve a global and fair promotion framework, with teachers who are willing to guide and orientate the activities after school hours, is not easy (35).…”
Section: Discussionmentioning
confidence: 99%